Maggie NELSON, "El arte de la crueldad", Madrid, Editorial Tres Puntos, 2020, 305 pp. - Guerrero, María Paz (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Maggie NELSON, El arte de la crueldad, Madrid, Editorial Tres Puntos, 2020, 305 pp.